Penerapan Akuntansi Lingkungan Pada Pam Tirta Karajae Kota Parepare (Analisis Akuntansi Syariah) - Moh. Yasin Soumena; Musmulyadi Musmulyadi; Syahriyah Semaun; Damirah Damirah; Isma Wulandari Pryatna (Jurnal Mirai Management, 2023)
Environmental accounting basically requires full awareness of companies that benefit from the environment. Environmental accounting is accounting in which it identifies, measures, presents, and discloses costs related to company activities related to the environment. The purpose of this study is to find out how to identify, measure, and disclose environmental accounting and analyze according to sharia accounting at PAM Tirta Karajae, Parepare City through three sharia accounting principles. This research uses a qualitative descriptive research method and is a type of field research. The results of the study show that 1) the application of environmental accounting at PAM Tirta Karajae, Parepare City, is not in accordance with existing standards. 2) how to measure costs, such as the cost of maintaining raw sources using rupiah units in the amount issued by the company and referring to the cost of realization of the previous period's budget and has disclosed environmental management in expenditure costs. 3) the way of identifying, measuring and disclosing in environmental accounting is not in accordance with the three principles of sharia accounting, because the identification of environmental accounting costs has not been shown in the financial statements, while the measurement and disclosure of environmental management costs only attaches maintenance costs to raw sources in expenditure costs. Keywords : Environmental Accounting, Tirta Karajae, Sharia Accounting Analysis